Branched-chain amino acids - Harris, Robert A. (Robert Allison), 1939-; Sokatch, J. R. (John Robert), 1928-2006 (Methods in enzymology ;, 1988)
This volume includes chapters on the newest techniques for measuring metabolites of branched-chain amino acids, many new enzyme assays such as the measurement of isozymes of acetohydroxacid synthase, and the purification of recently described enzymes such as isovaleryl-CoA dehydrogenase.